Electric scooters with focus on road safety and sustainability - Kabbara, Jawana; Alkhayyat, Serag (My University, 2022)
Rising e-scooter accidents in the last couple of years is an increasing concern in the European countries, including Sweden. The sudden surge of shared e-scooters in the Swedish cities beginning from the year 2018 resulted unfortunately in serious traffic accidents that are just increasing year by year. Considering the fact that these vehicles are growing in popularity, their potential as a main part of commuting in the future should be studied. This report is concerned with road safety and sustainability regarding e-scooters which is a new mobility solution that is rapidly expanding around the world. The main focus lies on Sweden but a specific section focuses only on the Swedish city of Gothenburg. Data collection as well as a survey are the methods that were used in order to create an overview of various facts and data regarding e-scooters. The results showed that shared e-scooters as a mobility solution is an easy, uncomplicated and pretty cheap way of traveling from a specific area to another. Nevertheless, this mobility solution saves time, is fun and is a convenient alternative for avoiding traffic jam. However, these scooters can be extremely dangerous if they are used unproperly. A huge concern related to traffic safety is that most users are still inexperienced which is resulting in serious injuries and fatalities. The users lack knowledge regarding the regulations of e-scooter usage as well as the safe behavior when driving these vehicles. To be specific, the users are acting in an unresponsible way by blocking sidewalks, speeding up, not wearing helmets, driving under the influence of alcohol, and sharing rides with others. Thus, different sides should take specific actions to make this new innovation safer. In addition, road defects, technical faults and the vehicles small size are some main risk factors that contribute to the traffic accidents. E-scooters are often introduced by e-scooter companies as an environmentally friendly method of transportation with no, or very little, footprint. However, this can only be true if the lifespan of these vehicles is neglected. Therefore, this is a controversial subject and the answer depends on what factors are being considered when examining the sustainability of these scooters.
Keywords: E-scooters; Traffic safety; Transportation; Road safety; Sustainability; Mobility